Sexual health and HIV in the Army. Issue 3 (11th July 2013) - Dufty, Ngozi E; Clay, K; Wilson, R; Watson, J
Abstract : Sexual acquisition of infections has always been an important part of military history and although disease patterns have changed over time, the problem has not gone away. This article will look at how to recognise infection, the general principles of management, where to access guidance and how to get specialised help within the complexities of the military environment.